Route Selection for Minerals’ Transportation to Ensure Sustainability of the Arctic - Ivan Potravny; Andrey Novoselov; Irina Novoselova; Katherine Yeshia Chávez Ferreyra; Violetta Gassiy (Sustainability, 2022)
The article addresses the issues of route selection for minerals’ transportation based on social, economic, and environmental factors to ensure sustainability in the Arctic. The case of the Tomtor deposit of rare earth metals in Yakutia is considered in the paper. The authors analyze its impact on traditional lands and the environment. To ensure sustainability and to optimize the natural resources’ use for route selection for minerals’ transportation in the Arctic, a system of criteria is proposed. It covers not only the cost of transportation and the distance from the deposit to the processing point, but also the damage to traditional lands of indigenous peoples, and environmental and social risks. An algorithm for choosing the optimal solution for the conservation of natural resources and traditional lands during the transportation of minerals is proposed. It depends on the developed criteria. The proposed approaches can be used during industrial development and investment in the Arctic to optimize the routes of mineral resources’ transportation.